Impact of the industrial revolution 4.0 on higher education in Vietnam: challenges and opportunities - Tri, Nguyen Minh; Hoang, Pham Duy; Dung, Nguyen Trung (Linguistics and Culture Review, 2021)
With a lofty goal and mission, it is the mission of "cultivating people". Higher education has an important role to play in the development of society. Education not only trains people with good knowledge and expertise, but also trains people with good moral and physical qualities, effectively serving the socio-economic development associations of each country, each ethnic group. The industrial revolution 4.0 with its rapid development speed and profound impacts on all areas of the social life of each country, if left behind of this revolution, the backward development is also inevitable. On the contrary, if you make good use of the advantages of this revolution, the opportunities are huge. In the digital era, higher education will change profoundly from the educational environment, the role of teachers and learners to teaching methods. Currently, not only Vietnam but also many countries around the world are facing the big challenge of a shortage of highly qualified, specialized and skilled workers. Therefore, in order to renovate higher education to meet the requirements of the labor market, it is necessary to raise awareness and renew thinking on higher education development; renovating training programs and methods.